Creating Virtual Corridors: Social Network Discovery and Landscape Patch Connectivity of Permaculture Projects and Initiatives on Facebook - Flores, Jabez Joshua M.; Obrero, Rick Jason; Gelisan, Luisa A.; Foronda, Edward Allan; Mendiola, Rikki Lee (International Journal on Open and Distance e-Learning, 2017)
Permaculture is a design system conceptualized in Australia in the 1970s in response to urgent environmental issues at that time. Mainstreamed via social media in recent years, permaculture is being practiced around the world on diverse landscapes. The study aimed to discover socio-spatial permaculture landscape networks based on a permaculture designer’s Facebook social network. Using social network theory and landscape ecology, the study simulated and predicted how permaculture designers would be able to create invisible landscape corridors called “virtual corridors.” Virtual corridors are determined by computing for the Percentage Linkage Strength (%LS) metric derived from data obtained from two scoring systems developed for the study: the Social Score (SS) and the Permaculture Score (PS). Two hundred eighty six network nodes were initially discovered to be potential permaculture designers via Facebook Group membership. The two scoring systems revealed the top ten network nodes with the highest computed %LS that created virtual corridors. A Meerkat Lite-generated sociogram overlayed on a Google Earth topographic map animated in Camtasia Studio were used to illustrate the discovered network. Then NetLogo was used to simulate and predict the virtual corridor creation process. In the future, the methodology could be used to determine potential study sites for transdisciplinary permaculture research and study the environmental impact of permaculture projects and initiatives on landscape patches. It would also provide practitioners and researchers a framework to better understand how a network of individual solutions could lead to macro-scale landscape patch management.